A U.S. energy bill at last. - Sweet, W. (IEEE spectrum)
This paper reports on a US Congress-approved comprehensive energy law to make electric power reliability rules mandatory so that the kinds of lapses on the part of utility managers that led to the big blackout of August 2003 will now be punishable. The energy bill also allocates billions of dollars for a variety of incentives to encourage energy efficiency and conservation as well as greater use of wind, solar, and nuclear energy.